1981
DOI: 10.3382/ps.0601873
|View full text |Cite
|
Sign up to set email alerts
|

An Apparent Rachitogenic Effect of Excessive Vitamin E Intakes in the Chick

Abstract: Three replicates (pens of 10 birds each) of a 2 X 2 factorial design experiment (25 and 10,000 IU vitamin E/kg diet on 25 and 500 IU vitamin D/kg diet) were utilized in order to assess effects of excessive intakes of vitamin E on calcium metabolism in the growing chick. A one-week equilibration period was followed by a two-week experimental period. Excessive vitamin E supplementation resulted in reduced calcium and phosphorus in blood plasma, in dry fat-free bone, and in bone ash, calcium, and phosphorus. Inad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…At Day 14, however,  and -tocopherol showed no effect on formation of the calcified nodules. These findings also indicate the inhibition of the differentiation to the osteoblasts producing osteoid, but not of the differentiation to the osteoblasts producing the calci- observed that excessive vitamin E supplementation reduced calcium and phosphorus in bone in chick [25]. From our result, it seems to be possible that the decrease of the amount of calcified bone matrix by vitamin E supplementation in chick was caused by inhibition of osteoid formation.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…At Day 14, however,  and -tocopherol showed no effect on formation of the calcified nodules. These findings also indicate the inhibition of the differentiation to the osteoblasts producing osteoid, but not of the differentiation to the osteoblasts producing the calci- observed that excessive vitamin E supplementation reduced calcium and phosphorus in bone in chick [25]. From our result, it seems to be possible that the decrease of the amount of calcified bone matrix by vitamin E supplementation in chick was caused by inhibition of osteoid formation.…”
supporting
confidence: 57%
“…Ebina et al reported that Fe-induced impairment of bone formation was prevented by dietary vitamin E supplementation in rats [13]. In addition, vitamin E stimulated trabecular bone formation in chicks [25]. Therefore, vitamin E is thought to affect bone formation and bone remodeling.…”
mentioning
confidence: 99%
“…However, there is evidence that massive dietary doses of this vitamin may cause various disorders (March et al, 1973;Murphy et al, 1981;Aburto and Britton, 1996). An adverse effect of excessive intake of vitamin E is its interference with cholecalciferol utilisation, particularly when the latter's dietary concentration is marginal.…”
Section: Introductionmentioning
confidence: 99%
“…An adverse effect of excessive intake of vitamin E is its interference with cholecalciferol utilisation, particularly when the latter's dietary concentration is marginal. This interference is manifested mainly by reduction in bone ash and body weight (March et al, 1973;Murphy et al, 1981;Aburto and Britton, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This is possibly due to the interaction of vitamin E with vitamin D. Excess of VE in the diet can reduce Ca and P in the blood and bone (Murphy et al, 1981), absorption and utilization of vitamin A and D 3 (Leeson & Summers, 2001). In this case the vitamin D is dissolved in the unhydrolyzed and possibly nonsolubilized tocopheryl acetate and passes through the gut unabsorbed, consequently impaired bone and shell calcification.…”
Section: Physical Quality Of Eggmentioning
confidence: 99%